Epistasis of the DRD2/ANKK1 Taq Ia and the BDNF Val66Met polymorphism impacts Novelty Seeking and Harm Avoidance - Montag, Christian; Markett, Sebastian; Basten, Ulrike; Stelzel, Christine; Fiebach, Christian; Canli, Turhan; Reuter, Martin (Neuropsychopharmacology, 2010)
Mounting evidence from animal studies show that the mesolimbic dopaminergic pathways are modulated by the brain-derived neurotrophic factor (BDNF). This study investigates in N=768 healthy Caucasian participants the influence of two prominent functional single-nucleotide polymorphisms (SNPs) on the BDNF gene (BDNF Val66Met SNP) and the ankyrin repeat and kinase domain containing 1 (ANKK1) gene (DRD2 Taq Ia/ANKK1 SNP) on the personality traits of Novelty Seeking and Harm Avoidance, which are mediated, in part, through dopaminergic mesolimbic circuitry. Carriers of the 66Met+/A1+ variant scored lowest on Novelty Seeking and highest on Harm Avoidance, compared to all other genotype groups. These participants are characterized by a relatively low D2 receptor density in the striatum and an impaired activity-dependent secretion of BDNF. This is one of the first genetic association studies to show a modulatory role for BDNF genetic variation on genetically mediated differences in the mesolimbic dopaminergic system in the context of human personality.